2022
DOI: 10.1093/eurheartj/ehac262
|View full text |Cite
|
Sign up to set email alerts
|

2022 ESC Guidelines for the management of patients with ventricular arrhythmias and the prevention of sudden cardiac death

Abstract: All experts involved in the development of these guidelines have submitted declarations of interest. These have been compiled in a report and published in a supplementary document simultaneously to the guidelines. The report is also available on the ESC website www.escardio.org/Guidelines See the European Heart Journal online for supplementary data that includes background information and detailed discussion of the data that have provided the basis of the guidelines.Click here to access the corresponding ESC C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
850
0
57

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,333 publications
(919 citation statements)
references
References 1,186 publications
12
850
0
57
Order By: Relevance
“…A multicenter pooled analysis showed that induction of sustained ventricular arrhythmia (VA) during electrophysiological study was associated with a higher future risk of sustained VA, and was associated with a potentially clinically meaningful outcome, particularly in asymptomatic patients with a spontaneous type 1 Brugada pattern ECG [ 14 ]. Therefore, programmed ventricular stimulation is a Class IIb (LOE B) recommendation in the latest 2022 ESC Guidelines on ventricular arrhythmias [ 1 ]. The young index patient in family 1 consulted us for a second opinion due to his spontaneous borderline Brugada type 1 ECG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter pooled analysis showed that induction of sustained ventricular arrhythmia (VA) during electrophysiological study was associated with a higher future risk of sustained VA, and was associated with a potentially clinically meaningful outcome, particularly in asymptomatic patients with a spontaneous type 1 Brugada pattern ECG [ 14 ]. Therefore, programmed ventricular stimulation is a Class IIb (LOE B) recommendation in the latest 2022 ESC Guidelines on ventricular arrhythmias [ 1 ]. The young index patient in family 1 consulted us for a second opinion due to his spontaneous borderline Brugada type 1 ECG.…”
Section: Discussionmentioning
confidence: 99%
“…Brugada syndrome (BrS) is a hereditary cardiac disorder and has been linked to genetic variants, mainly in the SCN5A gene [ 1 , 2 ], located on the short arm of chromosome 3 encoding the α-subunit of the sodium channel NaV 1.5 [ 3 ]. It is characterized by dynamic ST-segment elevations in leads V1-3, typically followed by negative T waves.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, variants in cardiomyopathy-associated genes have been identified in both apparently idiopathic sudden cardiac arrest survivors and unexplained sudden cardiac death victims, driving calls for a broader approach to genetic testing in these cohorts which have been acknowledged in recent guidelines. 7,9,[12][13][14][15] So, to take a step even further: "what of the proposition of population screening?" Population databases with genetic and clinical information have been used to investigate the prevalence and penetrance of inherited heart diseases.…”
Section: See Article By Nafissi Et Almentioning
confidence: 99%
“…11 The potential for arrhythmia to occur prior to overt structural disease in inherited cardiomyopathy is increasingly appreciated as “concealed cardiomyopathy.” Indeed, variants in cardiomyopathy-associated genes have been identified in both apparently idiopathic sudden cardiac arrest survivors and unexplained sudden cardiac death victims, driving calls for a broader approach to genetic testing in these cohorts which have been acknowledged in recent guidelines. 7,9,12–15…”
mentioning
confidence: 99%
“…Among the predictors of SCD, obesity (a well-established independent risk factor for cardiovascular diseases) has been found to increase arrhythmic risk (i.e., every 5-unit increment in BMI confers a 16% higher risk of SCD) [ 12 , 13 , 14 , 15 , 16 ]. When autopsy and toxicological testing fail to find any anomaly or there are macroscopic and/or microscopic anomalies whose significance is uncertain, molecular autopsy (i.e., post-mortem genetic testing) should be indicated [ 17 , 18 ]. Indeed, as stated by the Asia Pacific Heart Rhythm Society and the Heart Rhythm Society in 2020, molecular autopsy in young victims of autopsy-negative SDs should be considered a “public health priority”, allowing for public health interventions such as the clinical/genetic screening of the first-degree relatives [ 19 ].…”
Section: Introductionmentioning
confidence: 99%